A spin-tunable resistive switching device and a method for fabricating the same
Patent Information
- Application Number
- CN202611176925.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-05
- Publication Date
- 2026-10-23
- Estimated Expiration
- 2046-08-05
AI Technical Summary
[0005]有鉴于此,本发明提出了一种自旋可调阻变器件及其制备方法,以解决现有技术中钙钛矿电极难以为NiFe2O4提供高质量的外延生长界面,从而导致阻变器件难以同时兼具阻变和自旋特性的问题
(1)本发明通过在MgO单晶衬底上依次外延生长TiN导电底电极与NFO尖晶石功能层,构建了"MgO/外延TiN/外延NFO"全外延异质结构器件。TiN与MgO之间的晶体结构兼容性保证了底电极层的高质量外延成核,进而为NFO的外延生长提供了结构匹配的模板界面,使NFO薄膜中的尖晶石有序度、界面完整性与缺陷分布均处于可控状态。在此基础上,器件同时具备稳定的阻变特性与可利用的磁/自旋自由度,实现了电场与磁场对阻变行为的协同调控,为阻变-自旋多场耦合器件的工程化实现提供了完整的结构与工艺解决方案。
Smart Images

Figure CN122699560B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the technical field of resistive switching device fabrication, and more particularly to a spin-tunable resistive switching device and its fabrication method. Background Technology
[0002] With the continuous development of artificial intelligence, the Internet of Things, and edge computing, the demand for devices for storage-computing convergence, inductive-memory-computing integration, and low-power neuromorphic hardware is constantly growing. Oxide devices, which combine electrical resistivity and magnetic / spin degrees of freedom, can achieve coordinated control of multiple physical fields (electromagnetic and magnetic) within the same device unit. This is expected to overcome the performance limitations of traditional resistive memories that rely on a single electric field for control, and provide a new technological direction for the development of next-generation non-volatile memory and neuromorphic computing chips.
[0003] NiFe2O4 (NFO), as a typical spinel ferrite material, theoretically possesses both stable magnetic ordering and tunable defect / ion dynamics, making it an important candidate material for achieving multi-field synergistic control of resistive switching and spin switching. However, the spin-dependent properties of NFO are highly dependent on the integrity of its spinel crystal structure and epitaxial quality—once polycrystalline, antiphase domains, or interface defect enrichment occur in the film, its magnetic ordering and spin transport properties will significantly deteriorate, making it difficult to stably obtain reproducible multi-field controlled resistive switching behavior. In existing research, NFO films are usually combined with epitaxial conductive oxide electrodes (such as perovskite structure electrodes like SrRuO3 and LaSrMnO3) to construct devices; however, perovskite structure electrodes and spinel NFO have inherent differences in crystal structure type and epitaxial matching relationship, which easily introduces large structural mismatches and interface defects, restricting the formation of high-quality spinel epitaxial NFO films.
[0004] Chinese patent application CN102185107A discloses a resistive random access memory (NFO) based on a NiFe2O4 thin film and its fabrication method. It uses conventional conductive materials such as ITO or Pt as the bottom electrode, and prepares a NiFe2O4 thin film on the bottom electrode using chemical solution deposition or pulsed laser deposition. Then, a Pt, Au, or Cu top electrode is deposited to form a sandwich-structured memory device. The fabricated device exhibits stable high-to-low resistance state transition characteristics, good cycle read / write capability, and retention characteristics. This technical solution is the first to verify the resistive switching memory application potential of NiFe2O4 thin film materials. However, the ITO or Pt bottom electrode used lacks a lattice-matched relationship with NiFe2O4, making it difficult to provide a high-quality epitaxial growth interface for NiFe2O4. The crystal quality and spinel structure order of the resulting film are limited, which is insufficient to stably activate the magnetic / spin characteristics of the NFO, thus preventing magnetic field modulation of the resistive switching behavior. Summary of the Invention
[0005] In view of this, the present invention proposes a spin-tunable resistive switching device and its fabrication method to solve the problem that in the prior art, perovskite electrodes are difficult to provide a high-quality epitaxial growth interface for NiFe2O4, which makes it difficult for the resistive switching device to simultaneously possess both resistive and spin characteristics.
[0006] The technical solution of this invention is achieved as follows: This invention provides a method for fabricating a spin-tunable resistive switching device, comprising the following steps: S1. Pre-treat the MgO single crystal substrate to obtain the pre-treated MgO substrate; S2. TiN epitaxial film is grown on the surface of the pretreated MgO substrate by pulsed laser deposition at a first temperature to serve as the bottom electrode layer; S3. Without removing the sample, switch to an oxygen-containing atmosphere and use a pulsed laser to deposit a NiFe2O4 thin film as a functional layer on the surface of the bottom electrode layer at a second temperature, wherein the second temperature is higher than the first temperature. S4. A device window is formed on the surface of the functional layer by photolithography, and a top electrode layer is prepared by electron beam evaporation or magnetron sputtering deposition. The device is then stripped to obtain a spin-tunable resistive switching device.
[0007] Specifically, in step S1, organic residues and particulate contamination on the substrate surface are removed through pretreatment. In step S2, a TiN thin film is epitaxially grown on the substrate surface. This film has low resistivity, high thermal stability, and an atomically flat upper surface, providing an ideal template interface with structural matching and extremely low defect density for the subsequent epitaxial growth of the NFO functional layer. This fundamentally supports the multi-field control capability of the device from the material structure level. In step S3, the good structural compatibility and near-lattice matching relationship between the epitaxial TiN thin film layer and the spinel NFO are utilized to induce the NFO to grow in a directional manner via epitaxy, significantly suppressing the formation of antiphase domains and obtaining the functional layer. In step S4, a top electrode layer is prepared on the surface of the functional layer, thus fully realizing the construction of the "MgO / epitaxy TiN / epitaxy NFO / top electrode" fully epitaxial spin-tunable resistive switching device. This provides a standardized device platform for the comprehensive characterization and application integration of subsequent resistive switching characteristics, cycle stability, and multi-field control characteristics.
[0008] Based on the above technical solutions, preferably, the pretreatment in step S1 includes: cleaning the MgO single crystal substrate with a cleaning solution, the cleaning solution including acetone, ethanol and deionized water; and heat-treating the cleaned substrate at a temperature of 1100~1300℃ in an oxygen atmosphere, so as to eliminate surface adsorbed molecules and reconstruct an atomically flat step-platform surface morphology.
[0009] Based on the above technical solutions, preferably, in step S2, the bottom electrode layer is prepared by pulsed laser deposition, the first deposition temperature is 300~700℃, the laser frequency is 1~10Hz, the laser energy is 200~500mJ, and the deposition atmosphere is any one of vacuum, inert gas and nitrogen-containing atmosphere.
[0010] Traditional perovskite conductive oxides such as SrRuO3 and LaSrMnO3 have inherent structural differences from spinel NFO, introducing unavoidable structural mismatches and interface defects, leading to severe degradation of NFO epitaxial quality. In contrast, TiN possesses a cubic rock salt crystal structure isomorphic to MgO, enabling the production of high-quality epitaxial electrodes. High-quality epitaxial TiN conductive electrodes with consistent orientation and continuous lattice were obtained on MgO substrates through pulsed laser deposition. Limiting the temperature to 300~700℃ ensures that the deposited atoms have sufficient surface migration energy to achieve layer-by-layer epitaxial nucleation, while effectively suppressing the volatilization of N atoms and interfacial interdiffusion. When the temperature is too low, the migration energy of Ti and N atoms after reaching the MgO surface is insufficient, and they cannot fully address the lattice sites. This easily leads to the formation of disordered island structures or even amorphous interlayers during the nucleation stage, which disrupts the epitaxial orientation relationship between the film and the MgO substrate. When the temperature is too high, N atoms in TiN are easily volatilized and desorbed at high temperatures, resulting in stoichiometric deviation of the film (increased nitrogen vacancies), introducing additional defect states, and may cause interdiffusion at the TiN-MgO interface, damaging the interface integrity.
[0011] Based on the above technical solutions, preferably, in step S2, the thickness of the bottom electrode layer is 5~200 nm. When the thickness is too low, the film has not yet completed continuous film formation, which poses a risk of voids and discontinuous conductive paths. Furthermore, the merging interfaces between epitaxial islands introduce a large number of grain boundaries, leading to a sharp increase in in-plane resistivity and making it impossible to provide a uniform and stable current injection surface. As the thickness increases, the epitaxial relationship of the epitaxial TiN tends to be perfect, and the conductivity and structural continuity of the film gradually improve. However, when the thickness is too high, the accumulation of internal stress in the film may induce an increase in dislocation density or even film warping, while also adversely affecting the total thickness of the device and the control of the etching depth in subsequent processes.
[0012] Based on the above technical solutions, preferably, in step S3, the second temperature of the pulsed laser deposition process is 450~750℃, the laser frequency is 1~10Hz, the laser energy is 200~500mJ, and the deposition atmosphere is an oxygen-containing atmosphere.
[0013] The formation of spinel NFO structure requires Ni 2+ Fe 3+Ions achieve long-range ordered occupancy at octahedral and tetrahedral lattice sites. When the growth temperature is too low, the ion diffusion kinetics are insufficient, the spinel site order decreases, and disordered cation distribution (anti-spinel phase) and antiphase domains easily appear in the film, leading to weakened magnetic order, reduced spin polarizability, and difficulty in stably reproducing resistive switching properties. When the temperature is too high, the surface atom desorption and redox kinetics runaway caused by the high temperature will disrupt the stoichiometry of NFO and aggravate interdiffusion at the TiN / NFO interface, damaging the electrical performance of the bottom electrode and the interface integrity. In this invention, a step-by-step temperature strategy of "first growing TiN at a low temperature, then growing NFO at a high temperature" is adopted: TiN obtains a high-quality epitaxial structure at a lower temperature, and then the temperature is raised to 450~750℃ to meet the thermodynamic driving force required for NFO spinel crystallization. Without damaging the established TiN epitaxial template and interface integrity, the spinel order and magnetic order quality of NFO are maximized, further improving the epitaxial quality and interface integrity of NFO spinel.
[0014] Based on the above technical solutions, preferably, in step S3, the thickness of the functional layer is 5~300nm. When the thickness is too low, the NFO layer thickness is only equivalent to a few unit cells, resulting in insufficient film continuity. The formation and breakage behavior of the conductive filaments during the Set / Reset process are severely affected by quantum size effects, leading to an extremely narrow resistive switching window and poor cycle stability. At the same time, the small magnetic volume causes a significant decrease in the magnetic ordering temperature (Curie temperature), making it difficult to utilize room temperature magnetic properties. As the thickness increases, the formation path of the resistive switching conductive filaments tends to stabilize, and the magnetic ordering properties also increase with the increase of film volume, continuously improving device performance. However, when the thickness is too high, the operating voltage required for the Set process increases linearly with the increase of film thickness, leading to increased power consumption. In addition, the accumulation of thermal stress inside the excessively thick NFO layer may cause film cracking or epitaxial degradation, and the statistical dispersion of the resistive switching filament path in the thick film increases, affecting the inter-unit consistency of the device.
[0015] Based on the above technical solutions, preferably, in step S4, the material of the top electrode layer is any one of Au, Pt, TiN and W, and the thickness of the top electrode layer is 50~100nm.
[0016] Based on the above technical solutions, preferably, the electron beam evaporation rate is 2.5 nm / min; and the magnetron sputtering deposition power is 35~50 W.
[0017] Based on the above technical solution, preferably, step S4 further includes oxygen or vacuum annealing of the epitaxial structure, specifically including: annealing at 650~750℃ for 10... -6 ~10 -7 Vacuum annealing was performed at Pa.
[0018] Based on the above technical solutions, preferably, in step S2, a bottom electrode layer is prepared using a mask or photolithography-etching process. The bottom electrode layer is a strip-shaped epitaxial TiN bottom electrode array, forming a cross-bar array perpendicular to the top electrode. More preferably, the mask is a strip-shaped mask with a diameter of 20~100 μm; the mask shape in the photolithography-etching process is strip-shaped with a diameter of 20~100 μm, and AZ5214 amphoteric adhesive is used for photolithography.
[0019] More preferably, the fabrication process of the bottom electrode layer includes: Substrate cleaning: The substrate to be photolithographically cleaned and the photomask were placed in acetone, anhydrous ethanol and deionized water in sequence for ultrasonic cleaning for 5 minutes. Finally, they were dried with a nitrogen gun to remove dust and other impurities attached to the surface. Spin coating: The substrate is vacuum-adsorbed onto the spin coater, a small amount of photoresist is dropped on, and the photoresist is evenly spin-coated onto the surface of the substrate using a two-step spin coating process. Pre-baking: After the photoresist is homogenized, it needs to be pre-baked at 97 ℃ on a heating plate for 2 minutes. The purpose is to dry the solvent and moisture in the photoresist and improve the adhesion between the photoresist and the substrate. Pre-exposure: Mount the mask on the MJB4, place the substrate inside, and perform a 1.2 s pre-exposure. This completes the transfer of the mask pattern. Post-baking: After the pre-exposure is completed, post-baking is performed at a temperature of 115 ℃ for 2 min. During this process, the AZ5214 photoresist begins to change from its original positive resist properties to negative resist properties, and compounds that are difficult to dissolve in the developer are generated in the exposed areas. Post-exposure: This involves generalizing the exposure of the entire substrate without a photomask, allowing the photoresist in previously unexposed areas to recombine and form compounds readily soluble in the developer. The exposure time is 12 seconds. Development: Mix developer and deionized water in a 1:4 ratio. Use tweezers to place the substrate into the solution and gently shake for about 38 seconds. Then rinse with deionized water to avoid over-development. Finally, observe the photolithography effect under a microscope to obtain the bottom electrode layer.
[0020] The present invention also provides a spin-tunable resistive switching device, which is prepared by the preparation method described above.
[0021] The spin-tunable resistive switching device and its fabrication method of the present invention have the following advantages over the prior art: (1) This invention constructs a fully epitaxial heterostructure device, namely "MgO / epitaxylated TiN / epitaxylated NFO", by sequentially epitaxially growing a TiN conductive bottom electrode and an NFO spinel functional layer on a MgO single crystal substrate. The crystal structure compatibility between TiN and MgO ensures high-quality epitaxial nucleation of the bottom electrode layer, thereby providing a structurally matched template interface for the epitaxial growth of NFO, making the spinel order, interface integrity, and defect distribution in the NFO film controllable. On this basis, the device simultaneously possesses stable resistive switching characteristics and available magnetic / spin degrees of freedom, realizing the synergistic control of resistive switching behavior by electric and magnetic fields, and providing a complete structural and process solution for the engineering realization of resistive-spin multi-field coupled devices.
[0022] (2) The present invention uses TiN with a cubic rock salt structure as the bottom electrode, which has good matching with the MgO substrate in terms of structure type and lattice parameters. This fundamentally eliminates the structural incompatibility problem between the electrode layer and the functional layer, effectively reduces the mismatch defect density at the TiN / NFO interface, and ensures the structural integrity and spin characteristics repeatability of the NFO spinel epitaxial film.
[0023] (3) This invention employs a stepwise temperature deposition strategy of "low-temperature TiN growth and high-temperature NFO growth," precisely matching the optimal thermodynamic growth windows for each of the two materials. TiN deposition at a lower temperature effectively drives epitaxial nucleation while suppressing N atom volatilization and interdiffusion at the TiN / MgO interface, ensuring the stoichiometric accuracy and low resistivity of the bottom electrode. Subsequently, the temperature is raised to a higher temperature for NFO growth, which is then converted to Ni. 2+ with Fe 3+ The long-range ordered occupancy of ions at spinel lattice sites provides sufficient thermodynamic driving force to effectively suppress the formation of antiphase domains without damaging the established TiN epitaxial structure and interface quality.
[0024] (4) The device fabrication process of this invention is based on mature PLD thin film growth technology and standard photolithography-lifting process, which has good process compatibility; the device unit can be expanded into a cross-bar array structure composed of mutually perpendicular strip electrodes, supporting multi-unit integration and array-level consistency evaluation; at the same time, the optional oxygen or vacuum annealing post-processing further provides a means to adjust the order of NFO spinel and resistive switching window. The overall solution has adaptability to low-power neuromorphic computing and in-memory computing hardware applications in terms of material selection, process flow and device structure, without the need to introduce special process equipment or additional compatibility modifications. Attached Figure Description
[0025] To more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.
[0026] Figure 1 This is a schematic diagram of the substrate cleaning and pretreatment process of the present invention; Figure 2 This is a structural diagram of the spin-tunable resistive switching device prepared according to the present invention; Figure 3 This is an HRTEM image of the NFO / TiN / MgO heterostructure of the present invention; Figure 4 The XRD diffraction pattern of the NFO / TiN heterofilm of the present invention is shown below. Figure 5 This is a resistance-to-variance curve diagram of the NFO memristor of the present invention; Figure 6 This is a test diagram of the in-plane and out-of-plane magnetic properties of the crystalline NFO device of the present invention. Detailed Implementation
[0027] The technical solutions of the present invention will be clearly and completely described below with reference to the embodiments of the present invention. Obviously, the described embodiments are only a part of the embodiments of the present invention, and not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without creative effort are within the scope of protection of the present invention.
[0028] Example 1 This embodiment provides a spin-tunable resistive switching device and its fabrication method, such as Figure 1 As shown, it includes the following steps: (1) The MgO substrate was ultrasonically cleaned in sequence with acetone-ethanol-deionized water, dried, and then heat-treated at 1200℃. (2) The MgO substrate was placed into the PLD cavity for PLD deposition. The deposition temperature was 400℃, the laser frequency was 5Hz, the laser energy was 350mJ, and the deposition atmosphere was a nitrogen atmosphere. An epitaxial TiN film with a thickness of 100nm was deposited on the surface of the MgO substrate as the bottom electrode. (3) Without removing the sample, switch to an oxygen-containing atmosphere and heat to 550°C to deposit an epitaxial NiFe2O4 thin film with a thickness of 200 nm on the bottom electrode surface; (4) The device dimensions were defined using photolithography. An Au top electrode was deposited by electron beam evaporation and then stripped off. The electron beam evaporation rate was 2.5 nm / min, and the thickness of the top electrode layer was 80 nm, resulting in a MgO / TiN / NiFe2O4 / Au structure, thus obtaining a spin-tunable resistive switching device. The device structure is as follows: Figure 2 As shown, Figure 2 Image (a) is a 3D view of the device. Figure 2 (b) is a cross-sectional view of the device. Figure 2 (c) is a planar schematic diagram of the device.
[0029] Example 2 This embodiment provides a spin-tunable resistive switching device and its fabrication method, including the following steps: (1) The MgO substrate was ultrasonically cleaned in sequence with acetone-ethanol-deionized water, dried, and then heat-treated at 1100℃. (2) The MgO substrate was placed into the PLD cavity for PLD deposition. The deposition temperature was 300℃, the laser frequency was 1Hz, the laser energy was 200mJ, and the deposition atmosphere was a nitrogen atmosphere. An epitaxial TiN film with a thickness of 5nm was deposited on the surface of the MgO substrate as the bottom electrode. (3) Without removing the sample, switch to an oxygen-containing atmosphere, heat to 450°C, and deposit an epitaxial NiFe2O4 thin film with a thickness of 5 nm on the surface of the bottom electrode; (4) The device size is defined by photolithography. The Pt top electrode is deposited by electron beam evaporation and then stripped. The electron beam evaporation speed is 2.5 nm / min and the thickness of the top electrode layer is 50 nm. The MgO / TiN / NiFe2O4 / Pt structure is obtained, and the spin-tunable resistive switching device is obtained.
[0030] Example 3 This embodiment provides a spin-tunable resistive switching device and its fabrication method, including the following steps: (1) The MgO substrate was ultrasonically cleaned in sequence with acetone-ethanol-deionized water, dried, and then heat-treated at 1300℃. (2) The MgO substrate was placed into the PLD cavity for PLD deposition. The deposition temperature was 700℃, the laser frequency was 10Hz, the laser energy was 500mJ, and the deposition atmosphere was vacuum. An epitaxial TiN film with a thickness of 200nm was deposited on the surface of the MgO substrate as the bottom electrode. (3) Without removing the sample, switch to an oxygen-containing atmosphere and heat to 750°C to deposit an epitaxial NiFe2O4 thin film with a thickness of 300 nm on the bottom electrode surface; (4) The device size is defined by photolithography. The Au top electrode is deposited by electron beam evaporation and then stripped. The electron beam evaporation speed is 2.5 nm / min and the thickness of the top electrode layer is 100 nm. The MgO / TiN / NiFe2O4 / Au structure is obtained, and the spin-tunable resistive switching device is obtained.
[0031] Example 4 This embodiment provides a spin-tunable resistive switching device and its fabrication method, including the following steps: (1) The MgO substrate was ultrasonically cleaned in sequence with acetone-ethanol-deionized water, dried, and then heat-treated at 1200℃. (2) Fabrication of strip-shaped epitaxial TiN bottom electrode arrays on MgO substrates using masking or photolithography-etching processes, specifically including The substrate and photomask were ultrasonically cleaned in acetone, anhydrous ethanol, and deionized water for 5 min in sequence. The substrate was then vacuum-adsorbed onto a spin coater, and a small amount of photoresist was dropped onto it. The photoresist was then evenly spin-coated onto the substrate surface using a two-step spin coating process. After spin coating, the substrate was preheated at 97°C for 2 min on a heated plate. The photomask was then mounted on an MJB4, and the substrate was placed on it for a 1.2 s pre-exposure to transfer the photomask pattern. The substrate was then postheated at 115°C for 2 min and then exposed to the entire substrate for 12 s without the photomask. The developer and deionized water were mixed in a 1:4 ratio, and the substrate was gently shaken in the mixture for about 38 s using tweezers. The substrate was then rinsed with deionized water, and the photolithography effect was observed under a microscope to obtain the bottom electrode layer. (3) Pulsed laser deposition was performed on the surface of the strip-shaped epitaxial TiN bottom electrode. The deposition temperature was 725℃, the laser frequency was 5Hz, the laser energy was 350mJ, and the deposition atmosphere was oxygen atmosphere. An epitaxial NiFe2O4 thin film with a thickness of 200nm was deposited on the surface of the bottom electrode. (4) The device size is defined by photolithography. The Au top electrode is deposited by electron beam evaporation and then stripped. The electron beam evaporation speed is 2.5 nm / min and the thickness of the top electrode layer is 80 nm. A strip-shaped top electrode perpendicular to the bottom electrode is prepared to form a cross-bar array, thus obtaining the MgO / TiN / NiFe2O4 / Au structure and a spin-tunable resistive switching device.
[0032] Comparative Example 1 This comparative example provides a resistive switching device and its fabrication method, including the following steps: (1) The MgO substrate was ultrasonically cleaned in sequence with acetone-ethanol-deionized water, dried, and then heat-treated at 1200℃. (2) A perovskite-structured conductive oxide electrode layer (LaSrMnO3) is deposited on the substrate to obtain a conductive bottom electrode; (3) Without removing the sample, switch to an oxygen-containing atmosphere and heat to 725°C to deposit an epitaxial NiFe2O4 thin film with a thickness of 200 nm on the bottom electrode surface; (4) The device size is defined by photolithography. Au top electrode is deposited by electron beam evaporation and then stripped. The electron beam evaporation speed is 2.5 nm / min and the thickness of the top electrode layer is 80 nm. The MgO / TiN / NiFe2O4 / top electrode structure is obtained, and the spin-tunable resistive switching device is obtained.
[0033] Comparative Example 2 This comparative example provides a spin-tunable resistive switching device and its fabrication method. The fabrication method is the same as in Example 1, except that step (3) does not involve heating, i.e.: (3) Without removing the sample, switch to an oxygen-containing atmosphere and deposit an epitaxial NiFe2O4 thin film with a thickness of 200 nm on the bottom electrode surface at a deposition temperature of 400 °C.
[0034] Comparative Example 3 This comparative example provides a spin-tunable resistive switching device and its fabrication method. The fabrication method is the same as in Example 1, except that the temperature in step (3) is lower than that in step (2). (2) The MgO substrate was placed into the PLD cavity for PLD deposition. The deposition temperature was 600℃, the laser frequency was 5Hz, the laser energy was 350mJ, and the deposition atmosphere was a nitrogen atmosphere. An epitaxial TiN film with a thickness of 100nm was deposited on the surface of the MgO substrate as the bottom electrode. (3) Without removing the sample, switch to an oxygen-containing atmosphere and heat to 550°C to deposit an epitaxial NiFe2O4 thin film with a thickness of 200 nm on the bottom electrode surface.
[0035] Comparative Example 4 This comparative example provides a spin-tunable resistive switching device and its fabrication method. The fabrication method is the same as in Example 1, except that: (2) The MgO substrate is placed in the PLD cavity for PLD deposition. The deposition temperature is 250℃, the laser frequency is 5Hz, the laser energy is 350mJ, and the deposition atmosphere is a nitrogen atmosphere. An epitaxial TiN film with a thickness of 100nm is deposited on the surface of the MgO substrate as the bottom electrode.
[0036] Comparative Example 5 This comparative example provides a spin-tunable resistive switching device and its fabrication method. The fabrication method is the same as in Example 1, except that: (2) The MgO substrate is placed in the PLD cavity for PLD deposition. The deposition temperature is 750℃, the laser frequency is 5Hz, the laser energy is 350mJ, and the deposition atmosphere is a nitrogen atmosphere. An epitaxial TiN film with a thickness of 100nm is deposited on the surface of the MgO substrate as the bottom electrode.
[0037] Comparative Example 6 This comparative example provides a spin-tunable resistive switching device and its fabrication method. The fabrication method is the same as in Example 1, except that: (3) Without removing the sample, switch to an oxygen-containing atmosphere and heat to 400°C to deposit an epitaxial NiFe2O4 thin film with a thickness of 200 nm on the bottom electrode surface.
[0038] Comparative Example 7 This comparative example provides a spin-tunable resistive switching device and its fabrication method. The fabrication method is the same as in Example 1, except that: (3) Without removing the sample, switch to an oxygen-containing atmosphere and heat to 800°C to deposit an epitaxial NiFe2O4 thin film with a thickness of 200 nm on the bottom electrode surface.
[0039] Comparative Example 8 This comparative example provides a spin-tunable resistive switching device and its preparation method. The preparation method is the same as in Example 1, except that the thickness of the bottom electrode layer in step (2) is 4 mm.
[0040] Comparative Example 9 This comparative example provides a spin-tunable resistive switching device and its preparation method. The preparation method is the same as in Example 1, except that the thickness of the bottom electrode layer in step (2) is 205 mm.
[0041] Comparative Example 10 This comparative example provides a spin-tunable resistive switching device and its fabrication method. The fabrication method is the same as in Example 1, except that the thickness of the functional layer in step (3) is 4 mm.
[0042] Comparative Example 11 This comparative example provides a spin-tunable resistive switching device and its fabrication method. The fabrication method is the same as in Example 1, except that the thickness of the functional layer in step (3) is 305 mm.
[0043] Performance testing The resistive switching devices prepared in the examples and comparative examples were subjected to performance testing. The testing indicators included the following, and the test results are shown in Table 1.
[0044] Table 1 Performance Test Results
[0045] Figure 3The HRTEM interface characterization and crystal orientation relationship of the cross-section of the MgO / epipolar TiN / epipolar NiFe2O4 heterostructure are shown, in which... Figure 3 In the middle (a), the TiN / MgO epitaxial interface is shown, indicating that the preparation process in this embodiment yielded a good epitaxial structure; Figure 3 In the middle (a1), the FFT diffraction pattern of TiN is shown. Figure 3 In the middle (a2), the FFT diffraction pattern of the epitaxial interface is shown. Figure 3 In the middle (a3), the FFT diffraction pattern of MgO is shown. Figure 3 (b) is an atomic image of NFO. Figure 3 (b1) is the FFT diffraction pattern of NFO.
[0046] Figure 4 The XRD patterns of MgO / epitaxial TiN / epitaxial NiFe2O4 thin films are shown. As can be seen from the figure, MgO / TiN shows diffraction peaks of MgO(200) and TiN(200), while MgO / TiN / NFO shows diffraction peaks of MgO(200), TiN(200), and NFO(400), indicating that the epitaxial process in this embodiment yielded a very good NFO(400) crystal.
[0047] Figure 5 The IV curve of the spin-tunable resistive switching device prepared in Example 1 is shown. As can be seen from the figure, it has a memristor window. The high / low resistance values of the device at -0.09V are 1.73MΩ (HRS) and 6kΩ (LRS), respectively. The on / off ratio HRS / LRS≈280. The binary values stored in the resistor correspond to the two high and low resistance values (HRS and LRS) of RESET, that is, logic 1 / 0, indicating that the device can respond stably under the action of an electric field.
[0048] Figure 6 The figure shows the resistance threshold / resistance state tunability and magnetic (MH) characteristics of the spin-tunable resistive switching device prepared in Example 1 under an applied magnetic field. As can be seen from the figure, hysteresis exists, the device exhibits out-of-plane in-plane polarization, and in-plane magnetization is more easily achieved. At high fields (approximately ±4000 Oe), the IP is approximately ±15–16 emu / cm. 3 OOP is approximately ±10–12 emu / cm 3 The binary representation of magnetic storage corresponds to two stable states (+M) in the magnetization direction. s With –M s (i.e., logic 1 / 0) indicates that the device can respond stably under the influence of a magnetic field.
[0049] As shown in Table 1, the spin-tunable resistive switching device prepared by the technical solution of the present invention not only suppresses leakage caused by interface and bulk defects, but also ensures the full formation of the low-resistance channel. Therefore, the high-resistance state has a higher resistance value and the low-resistance state has a lower resistance value, and the overall switching ratio is far superior to that of the comparative examples.
[0050] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the protection scope of the present invention.
Claims
1. A method for fabricating a spin-tunable resistive switching device, characterized in that, Includes the following steps: S1. Pre-treat the MgO single crystal substrate to obtain the pre-treated MgO substrate; S2. A TiN epitaxial film is epitaxially grown on the surface of a pretreated MgO substrate by pulsed laser deposition at a first temperature to serve as the bottom electrode layer; the first deposition temperature is 300~700℃, and the thickness of the bottom electrode layer is 5~200 nm. S3. Without removing the sample, switch to an oxygen-containing atmosphere and epitaxially grow a NiFe2O4 thin film as a functional layer on the surface of the bottom electrode layer by pulsed laser deposition at a second temperature, wherein the second temperature is higher than the first temperature; the second temperature of pulsed laser deposition is 450~750℃, and the thickness of the functional layer is 5~300nm. S4. A device window is formed on the surface of the functional layer by photolithography, and a top electrode layer is prepared by electron beam evaporation or magnetron sputtering deposition. The device is then stripped to obtain a spin-tunable resistive switching device.
2. The method for fabricating a spin-tunable resistive switching device as described in claim 1, characterized in that: In step S2, the bottom electrode layer is prepared by pulsed laser deposition with a laser frequency of 1~10Hz, a laser energy of 200~500mJ, and a deposition atmosphere of any one of vacuum, inert gas, and nitrogen-containing atmosphere.
3. The method for fabricating a spin-tunable resistive switching device as described in claim 1, characterized in that: In step S3, the laser frequency of the pulsed laser deposition process is 1~10Hz, the laser energy is 200~500mJ, and the deposition atmosphere is an oxygen-containing atmosphere.
4. The method for fabricating a spin-tunable resistive switching device as described in claim 1, characterized in that: In step S4, the material of the top electrode layer is any one of Au, Pt, TiN and W, and the thickness of the top electrode layer is 50~100nm.
5. The method for fabricating a spin-tunable resistive switching device as described in claim 1, characterized in that: In step S4, the electron beam evaporation rate is 2.5 nm / min; the magnetron sputtering deposition power is 35~50 W.
6. The method for fabricating a spin-tunable resistive switching device as described in claim 1, characterized in that: Step S4 also includes vacuum annealing of the epitaxial structure, specifically including: annealing at 650~750℃ for 10 minutes. -6 ~10 -7 Vacuum annealing was performed at Pa.
7. The method for fabricating a spin-tunable resistive switching device as described in claim 1, characterized in that: In step S2, a bottom electrode layer is prepared using a mask or photolithography-etching process. The bottom electrode layer is a strip-shaped epitaxial TiN bottom electrode array, which forms a cross-bar array perpendicular to the top electrode.
8. A spin-tunable resistive switching device, characterized in that: The spin-tunable resistive switching device is prepared using the preparation method described in any one of claims 1 to 7.
Citation Information
Patent Citations
Resistance-type random storage component and preparation method thereof
CN102185107A
Electric-activation-free NiFe2O4 resistive random access memory and preparation method thereof
CN115802881A
Preparation method, regulation and control method and application of Ni / NiO resistive device
CN121941274A